Competence Management and Competitive Product Development Concept and Implications for Practice - Chursin, Alexander (Springer International Publishing, 2018)
This monograph provides theoretical and practical perspectives on competency management as a key resource for producing competitive products. The authors develop and substantiate a law of dependence between competencies and emergence of new markets, and describe the practical aspects of developing competencies in high-tech companies. Further, they develop economic and mathematical models for managing the competitive advantages of a company based on competencies. Using these models, they present a method for evaluating and ranking core competencies, as well as for multi-criteria ratings of human potential efficiency. The book also discusses the mechanisms of competitiveness management based on a conceptual model of a competence center network. .